The practical encyclopedia of feng shui - Hale, Gill (London, United Kingdom : Lorenz Books, 1999)
An illustrated guide to the ancient art which uses aspects of home, office, and garden planning, arranging and decoration to promote and enhance general well-being in a person's life.
Feng shui in the home -- Feng shui in the garden -- The feng shui office
Includes index.